Thermal radiation effects on mhd with flow heat and mass transfer in casson nanofluid over a stretching sheet - Kho, Yap Bing; Abid, Hussanan; Norhafizah, Md Sarif; Zulkhibri, Ismail; Mohd Zuki, Salleh (EDP Sciences, 2018)
The boundary layer heat and mass transfer flow of Casson nanofluid over a stretching sheet with constant wall temperature (CWT) under the magnetic field and thermal radiation effects is investigated numerically. Using similarity transformations, the governing equations are reduced to a set of nonlinear ordinary differential equations (ODEs). These equations are solved numerically by Shooting method. The effects of Casson parameter, magnetic parameter, porosity parameter, radiation parameter, Prandtl number, Brownian parameter and thermophoresis parameter on velocity, temperature and concentration fields are shown graphically and discussed. The results show that increase in Casson parameter causes the wall temperature increase well in the nanofluid.